(untitled) (Revista "Boletín el Conuco", 2021)
The purpose of this article is to present a theoretical approach on creative accounting as an object of study; where the etymology of the term creativity has been distorted in the accounting discipline, homolocating this concept with that of fraud, being erroneously interpreted, associating it with those fraudulent acts carried out by the professional when manipulating their knowledge. In accordance with the above, this research focuses on describing the application of creativity criteria by professionals of the accounting sciences of the city of Villavicencio in their exercise, in the last five years. Instruments such as interviews and analysis of documents obtained from databases and repositories were used for the development of the study.